Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s13105-013-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular damage in obese female rats with hypoestrogenism

Abstract: Increase in body weight and adiposity has deleterious consequences on health. The aim of this study was to compare morphological and metabolic changes in the arterial vessels of Wistar rats with conditions of obesity, hypoestrogenism, and hypoestrogenism plus obesity. Ovariectomized rats (hypoestrogenic condition) received 30 % sugar in drinking water plus standard diet during 10 weeks. The hypoestrogenic-obese (HE-OB) group presented increase in weight, blood pressure, hypertriglyceridemia, and hyperglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Under this condition, there is an increase in food intake, body weight, and visceral adipose tissue. This, in turn, leads to other alterations, such as oxidative stress, inflammation, glucose intolerance, insulin resistance, dyslipidemia, hypertension, and hepatic and pancreatic damage, which can be exacerbated by hypercaloric food intake and aging . Accordingly, our data showed that HEOb rats exhibited a higher increase in caloric intake, body weight, adipose tissue, and oxidative stress than HE rats; indeed, Cap, Ex, and Cap + Ex treatments have higher effects in HEOb rats.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Under this condition, there is an increase in food intake, body weight, and visceral adipose tissue. This, in turn, leads to other alterations, such as oxidative stress, inflammation, glucose intolerance, insulin resistance, dyslipidemia, hypertension, and hepatic and pancreatic damage, which can be exacerbated by hypercaloric food intake and aging . Accordingly, our data showed that HEOb rats exhibited a higher increase in caloric intake, body weight, adipose tissue, and oxidative stress than HE rats; indeed, Cap, Ex, and Cap + Ex treatments have higher effects in HEOb rats.…”
Section: Discussionmentioning
confidence: 55%
“…At 1 week after surgery, animals received a carbohydrate‐based hypercaloric diet to induce obesity, as previously reported . Briefly, during a 28 week period, HEOb rats were given 300 g L −1 refined sucrose (Ingenio Azucarero el Potrero, Veracruz, Mexico) in their drinking water ad libitum , whereas HE rats were given tap water.…”
Section: Methodsmentioning
confidence: 99%
“…The ovariectomized female rat model has been commonly used to study the underlying mechanisms of pain perception associated with obesity [Stubbins et al, 2012;Da Silva et al, 2014] where a high sucrose (30%) diet can induce obesity [Kawasaki et al, 2005;Lima-Mendoza et al, 2014]. The aim of the present study was to analyse pain sensitivity using thermal stimuli (plantar test) over a 24 week period using a high sucrose diet in ovariectomized and na€ ıve Wistar rats to clarify the behavioural response to a nociceptive stimuli at various stages of weight gain.…”
Section: Introductionmentioning
confidence: 99%